The impact of the Covid-19 pandemic on the international labor market - Dluhopolska, Tetiana; Khita, Mariana (Herald of Economics, 2022)
Introduction. The COVID-19 pandemic has led to significant changes in labor markets around the world. Extraordinary political efforts have been made to overcome the effects of the corona crisis. Governments, together with trade unions, have taken immediate action to address the challenges posed by the COVID-19 pandemic, including the protection of jobs, including financial support for businesses and households experiencing sharp declines in income.Purpose. Justify the impact of the COVID-19 pandemic on the international labor market.Methods. The following methods were used in the research process: decomposition – to form the purpose of the research and set tasks; theoretical and methodological – to reveal the theoretical aspects of the international labor market; economic analysis – to study the regional and sectoral aspects of the impact of the COVID-19 pandemic on the international labor market; synthesis, comparison, analogy – to study the consequences of the COVID-19 pandemic for regional labor markets; logical generalization – to identify problems in the functioning of the international labor market caused by the COVID-19 pandemic; graphical method – to visualize the results of the study.Results. The COVID-19 pandemic has had a negative impact on the participation of the population in the labor force, reducing employment in all regions of the world with different income levels, both men and women, as well as increasing unemployment. Empirical analysis has shown that the greatest decline in employment among both men and women is observed in countries with incomes below and above average. In 2020, compared to 2019, the total working time in the world decreased by about 8.8 %, which is equivalent to the full-time work of 255 million employees. The loss of working time was particularly severe in Latin America and the Caribbean (16.2 %), Southern Europe and South Asia, and the total loss of working time in North and South America was 13.7 %. Overall, the COVID-19 crisis affected global working hours by about four times more than the global economic crisis of 2008-2009. The decline in employment was highest in the United States and lowest in Europe and Central Asia, where working hours were offset by job retention schemes. Many people have become inactive in the labor market because they did not see the opportunity to find a job successfully or simply could not search for it due to quarantine restrictions caused by the spread of the global pandemic. It should be noted that in high-income countries the unemployment rate in the period 2019-2020 (2.0 %) was very close to that observed in the period 2008-2009 (2.1 %). The female part of the working population suffered more from the decline in employment than the male. Young workers in all regions and groups of countries were particularly affected by the 2020 crisis, which led to a reduction in their employment by 8.7% compared to 3.7% among adults.Discussion. The COVID-19 pandemic has hit businesses and the informal economy hardest. Most informal enterprises are characterized by low productivity, low savings and investment, and scarce capital accumulation, which makes them particularly vulnerable to financial and economic shocks. Most workers could not afford to stop working because it would mean that they would not be able to meet their basic needs (such as food). Where markets and trading floors were closed during a harsh lockdown or curfew, the incomes of many informal workers, especially street vendors, disappeared instantly, putting them at risk of access to food. Informal homeworkers who produce goods or services for local, national or global supply systems have lost commercial orders from customer companies and in many cases have not been able to get paid for previously executed orders. Refugees and migrant workers have also been particularly affected by the economic consequences of the COVID-19 pandemic. They are mainly concentrated in sectors with high levels of temporary, informal or unprotected employment, characterized by low wages and lack of social protection. For many migrants, losing their job not only directly affects their own income, but also reduces their remittances. The post-pandemic period will be a time of building the future by creating new jobs, but this will only happen if effective labor market policies are implemented at both the national and global levels.